2018
DOI: 10.1007/s10554-018-1406-1
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic features of PFOs and paradoxical embolism: a complicated puzzle

Abstract: Patent foramen ovale (PFO) is a residual, oblique, slit or tunnel like communication in the atrial septum that persists into adulthood. It is usually an incidental finding with no clinical repercussions. Nevertheless, recent evidence supports the association between the presence of a PFO and a number of clinical conditions, most notably cryptogenic stroke (CS). There is enough evidence that paradoxical embolism is a mechanism which can explain this association. Patient characteristics and certain echocardiogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…The DEFENCE trial not only breaks the spear in favor of PFO device closure over medical therapy in reducing the risk of recurrent cryptogenic stroke but also suggests greater effectiveness of device closure in patients with high-risk anatomic PFO features. Albeit this trial reported a PFO size cutoff value of 2 mm, the presence of a large PFO (3 mm) has been previously related to increased recurrence of ischemic stroke (Lee et al 2010), and a distinction between small (1.9 mm), medium (2À3.9 mm) and large (4 mm) PFOs has been proposed (Aggeli et al 2018).…”
Section: Indications For Transcatheter Closurementioning
confidence: 91%
“…The DEFENCE trial not only breaks the spear in favor of PFO device closure over medical therapy in reducing the risk of recurrent cryptogenic stroke but also suggests greater effectiveness of device closure in patients with high-risk anatomic PFO features. Albeit this trial reported a PFO size cutoff value of 2 mm, the presence of a large PFO (3 mm) has been previously related to increased recurrence of ischemic stroke (Lee et al 2010), and a distinction between small (1.9 mm), medium (2À3.9 mm) and large (4 mm) PFOs has been proposed (Aggeli et al 2018).…”
Section: Indications For Transcatheter Closurementioning
confidence: 91%
“…Several studies support that one of the most powerful markers of a non-incidental PFO in stroke patients is young age, usually defined as age ≤ 55 years (1,16,35,36). The incidence of PFO in the stroke population tends to decrease with increasing age (0-30 years: 34.3%, 30-80 years: 25.4%, 90-100 years: 20.2%),while other more traditional stroke risk factors, such as hypertension, dyslipidemia, smoking, and arrhythmias increase (2,5,22).…”
Section: Agementioning
confidence: 99%
“…In most studies, size is an independent risk factor for stroke occurrence and recurrence (1,5,39,40), with OR of 2.54 when the size is ≥2 mm (41). Moreover, CS patients tend to have larger PFOs, when compared to stroke patients of other known causes (13,36).…”
Section: High-risk Anatomical Features Of Pfomentioning
confidence: 99%
“…On the contrary, in endocardiac shunts, the shunt is dependent on pressure difference between right and left atrium and it is affected by breathing pattern and Valsalva maneuver. Microbubbles are typically seen within the first 3 cardiac cycles [93,94]. Because in HPS shunt worsens in the upright position, this body position may facilitate microbubbles passage in the left cardiac chambers [92].…”
Section: Hepatopulmonary Syndrome and Portopulmonary Hypertension: Cumentioning
confidence: 99%